Intraoperative Indocyanine Green Fluorescence Angiography—An Objective Evaluation of Anastomotic Perfusion in Colorectal Surgery. Issue 6 (June 2015) - Protyniak, Bogdan; Dinallo, Anthony M.; Boyan, William P.; Dressner, Roy M.; Arvanitis, Michael L.
The essentials for any bowel anastomosis are: adequate perfusion, tension free, accurate tissue apposition, and minimal local spillage. Traditionally, perfusion is measured by assessing palpable pulses in the mesentery, active bleeding at cut edges, and lack of tissue discoloration. However, subjective methods lack predictive accuracy for an anastomotic leak. We used intraoperative indocyanine green (ICG) fluorescence angiography to objectively assess colon perfusion before a bowel anastomosis. Seventy-seven laparoscopic colorectal operations, between June 2013 and June 2014, were retrospectively reviewed. The perfusion to the colon and ileum was clinically assessed, and then measured using the SPY Elite Imaging System. The absolute value provided an objective number on a 0–256 gray-scale to represent differences in ICG fluorescence intensity. The lowest absolute value was used in data analysis for each anastomosis (including small bowel) to represent the theoretical least perfused/weakest anastomotic area. The lowest absolute value recorded was 20 in a patient who underwent a laparoscopic right hemicolectomy for an adenoma, with no postoperative complications. Four low anterior resection patients had additional segments of descending colon resected. There was one mortality in a patient who underwent a laparoscopic right hemicolectomy. This study illustrates an initial experience with the SPY system in colorectal surgery. The SPYprovides an objective, numerical value of bowel perfusion. However, evidence is scant as to the significance of these numbers. Large-scale randomized controlled trials are required to determine specific cutoff values correlated with surgical outcomes, specifically anastomotic leak rates.